Advance on the absorption, metabolism, and efficacy exertion of quercetin and its important derivatives: Absorption, metabolism and function of quercetin. Issue 4 (2nd November 2020) - Hai, Yu; Zhang, Yuanxiao; Liang, Yingzhi; Ma, Xiaoyu; Qi, Xiao; Xiao, Jianbo; Xue, Weiming; Luo, Yane; Yue, Tianli
Abstract: Quercetin, a dietary flavonol, has been used as potential ingredient in food supplements to promote health. Its health effects are closely related to its bioavailability and further depend on its absorption, metabolism and excretion in vivo . Here, we systematically summarized the absorption and metabolism of quercetin in human intestine, liver, and kidney, highlighting the transport and metabolic pathways, intermediate metabolites, and circulation channels involving quercetin. The bioactivities of quercetin on theintestine, liver, and kidney were also considered. In general, except for passive diffusion, different transporters (e.g., SGLT1, OATPs, and MRPs) participate in the transport of quercetin and its metabolites across biological barriers. Quercetin undergoes phase II metabolism after absorption by the intestine and is finally excreted into bile through liver or urine through kidney. Quercetin can protect the intestinal barrier and modulate the microflora. Moreover, its antioxidant, anti‐inflammatory, and anti‐fibrotic activities protect the liver and kidney. Abstract : Health effects of quercetin are closely related to its bioavailability and further depend on its absorption, metabolism, and excretion in vivo . After being absorbed via passive diffusion or transportation mediated by different transporters, it mainly undergoes phase II metabolism included glucuronidation, sulfation, and methylation reactions. Quercetin can protect the intestinal barrier and modulate the intestinal microbiota composition, meanwhile, its antioxidant, anti‐inflammatory, and anti‐fibrosis properties protect the liver and kidney